2021
DOI: 10.3389/fneur.2021.625308
|View full text |Cite
|
Sign up to set email alerts
|

Overview of MR Image Segmentation Strategies in Neuromuscular Disorders

Abstract: Neuromuscular disorders are rare diseases for which few therapeutic strategies currently exist. Assessment of therapeutic strategies efficiency is limited by the lack of biomarkers sensitive to the slow progression of neuromuscular diseases (NMD). Magnetic resonance imaging (MRI) has emerged as a tool of choice for the development of qualitative scores for the study of NMD. The recent emergence of quantitative MRI has enabled to provide quantitative biomarkers more sensitive to the evaluation of pathological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 80 publications
2
47
0
Order By: Relevance
“…Manual segmentation is a bottleneck, and therefore a major limitation in the application of qMRI in clinical studies. This has driven researchers towards developing automated solutions using algorithmic machine learning solutions [7]. Defining each muscle separately and segmenting an image into n labels can be framed as a categorization problem where the goal is to find the right category for each voxel in the image.…”
Section: Introductionmentioning
confidence: 99%
“…Manual segmentation is a bottleneck, and therefore a major limitation in the application of qMRI in clinical studies. This has driven researchers towards developing automated solutions using algorithmic machine learning solutions [7]. Defining each muscle separately and segmenting an image into n labels can be framed as a categorization problem where the goal is to find the right category for each voxel in the image.…”
Section: Introductionmentioning
confidence: 99%
“…Since diffusion metrics vary between different muscle groups in healthy controls and NMD, muscle segmentation has an important role in the analysis of mDTI data [ 3 ]. In NMD, the segmentation process is even more challenging because fatty infiltration, increase in connective tissue, and inflammation complicate differentiation of different muscle groups [ 12 ]. In this study, two evaluated segmentation techniques—MSB and VBT—showed excellent inter-rater reliability in healthy and dystrophic muscles and, therefore, a low rater dependency despite a high degree of fatty infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…A high degree of fat infiltration can complicate muscle segmentation due to deviating anatomy [ 10 ]. Since automatic segmentation algorithms are still in evaluation, muscle segmentation is usually done manually [ 11 , 12 ]. As manual segmentation is time- and cost-consuming and NMD are rare diseases, the pooling of data plays an important role in the application in clinical studies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent technique is volume‐based analysis, which can be performed using full manual segmentation or semiautomatic segmentation to separate individual muscles 10 . Semiautomatic segmentation techniques are increasingly popular in mDTI analysis because they provide similar accuracy as full manual segmentations and reduce the segmentation time 11,12 . By contrast, classic ROI‐based tractography has to be performed manually and requires a large amount of time and an experienced examiner 9 .…”
Section: Introductionmentioning
confidence: 99%